The altering eye contemporary international cinema - Kolker, Robert Phillip; Open Book Publishers (Open Book Publishers, 2009)
"The Altering Eye covers a "golden age" of international cinema from the end of WWII through to the New German Cinema of the 1970s. Combining historical, political, and textual analysis, Kolker develops a pattern of cinematic invention and experimentation from neorealism through the modernist interventions of Jean-Luc Godard and Rainer Maria Fassbinder, focusing along the way on such major figures as Luis Buñuel, Joseph Losey, the Brazilian director Glauber Rocha, and the work of major Cuban filmmakers. Kolker's book has become a much quoted classic in the field of film studies providing essential reading for anybody interested in understanding the history of European and international cinema. This new and revised edition includes a substantive new preface by the author and an updated bibliography."--Publisher's website.
New Preface -- Introduction -- 1. The Validity of the Image -- 2. The Substance of Form -- 3. Politics, Psychology, and Memory -- Notes -- Annotated Bibliography -- Selected Bibliography on European Cinema Since 1983 -- Index.
"First edition published in 1983 by Oxford University Press"--Verso of t.p.
Available through Open Book Publishers.
Includes bibliography (pages 299-313) and index.
Mode of access: World Wide Web.
Keywords: Motion picture plays -- History and criticism; Motion pictures -- Philosophy